Digital Business Model Development through the Implementation of a Smart Tuition Payment System - Laqma Fitrani; Angga Lisdiyanto; Masti Fatchiyah Maharani; Yerezqy Bagus; Dina Zatusiva Haq (Jurnal Teknologi Informatika dan Komputer, 2026)
The tuition payment system is an essential component of school financial administration that supports educational operations. However, many schools still rely on manual or semi-digital payment processes, which often result in delayed transaction recording, data entry errors, and limited transparency in financial reporting. This study aims to develop a web-based online tuition payment application to improve the efficiency, accuracy, and transparency of school financial management. The research employed a qualitative descriptive approach with data collected through observation, interviews, and literature review. System development was conducted using the Agile method, allowing the application to be refined iteratively according to user needs. The system was implemented using PHP and MySQL and includes features such as student data management, tuition billing generation, payment recording, digital receipt generation, and real-time financial reporting. The results indicate that the developed system enhances administrative efficiency, reduces recording errors, and improves the timeliness and transparency of financial reports. Furthermore, the implementation of this system supports the achievement of Sustainable Development Goal (SDG) 4: Quality Education by strengthening governance and sustainability in educational services.